2016
DOI: 10.1007/s10964-016-0468-4
|View full text |Cite
|
Sign up to set email alerts
|

London Education and Inclusion Project (LEIP): Results from a Cluster-Randomized Controlled Trial of an Intervention to Reduce School Exclusion and Antisocial Behavior

Abstract: School exclusion as a disciplinary measure remains a controversial issue. In spite of numerous attempts to reduce this practice, no solutions with documented effectiveness exist. This article reports results of a cluster-randomized controlled field trial carried out in 36 schools across London. The trial is an independent evaluation of a 12-week-long intervention, Engage in Education-London (EiE-L), delivered by Catch22. The intervention was aimed at students in secondary school who are most at risk of school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…If the final report produced data for the same variables originally proposed to be tested, we concluded there was a low risk of bias (e.g. Bradshaw et al 2012;Lewis et al 2013;Obsuth et al 2016). It is important to mention that many of our included studies were unpublished PhD theses (i.e.…”
Section: ; Smith 2004)mentioning
confidence: 97%
See 3 more Smart Citations
“…If the final report produced data for the same variables originally proposed to be tested, we concluded there was a low risk of bias (e.g. Bradshaw et al 2012;Lewis et al 2013;Obsuth et al 2016). It is important to mention that many of our included studies were unpublished PhD theses (i.e.…”
Section: ; Smith 2004)mentioning
confidence: 97%
“…Exceptionally, the review involved three manuscripts published in 2016. In the first case (Obsuth et al 2016), the registered protocol of the study had been identified in our electronic searches and we were waiting for the final report. Sprague et al (2016) was sent to us, because it included more information than a previous published version of the study published in previous years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings demonstrate that, in addition to victimization, subtle forms of exclusion may impede the social integration of immigrant youth. This line of research, along with others that focus on other forms of exclusion including those relating to one's identity (e.g., gender identity, Wernick et al 2017) or one's actions (e.g., exclusions from school, e.g., Obsuth et al 2017) has become one of the most important areas of youth research and policy (see Levesque 2015a, 2017a) of our time.…”
mentioning
confidence: 98%